2015
DOI: 10.1101/021857
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The distribution and impact of common copy-number variation in the genome of the domesticated apple,MalusxdomesticaBorkh

Abstract: Background: Copy number variation (CNV) is a common feature of eukaryotic genomes, and a growing body of evidence suggests that genes affected by CNV are enriched in processes that are associated with environmental responses. Here we use next generation sequence (NGS) data to detect copy-number variable regions (CNVRs) within the Malus x domestica genome, as well as to examine their distribution and impact. Methods: CNVRs were detected using NGS data derived from 30 accessions of M. x domestica analyzed using … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…The results of experimental evolution experiments suggest that CNVs contribute to the rapid adaptation associated with domestication and during population expansion of the domesticated species. Advances in detection methodologies (summarized in Box 1), reduced sequencing costs, and proliferation of sequencing data have expanded CNV studies, and CNVs have been described in most major crop plant species, including rice, maize, potato, soybean, barley, cucumber, melon, apple, and grapevine ( Table 1, Key Table) [ [29][30][31][32][33][34][35][36][37]. Not surprisingly, they have also been examined in domesticated animal species, such as silkworm, sheep, goat, pig, chicken, cow, horse, and dog (Table 1) [22,[38][39][40][41][42][43].…”
Section: Cnvs Are Widespread In Domesticated Speciesmentioning
confidence: 99%
“…The results of experimental evolution experiments suggest that CNVs contribute to the rapid adaptation associated with domestication and during population expansion of the domesticated species. Advances in detection methodologies (summarized in Box 1), reduced sequencing costs, and proliferation of sequencing data have expanded CNV studies, and CNVs have been described in most major crop plant species, including rice, maize, potato, soybean, barley, cucumber, melon, apple, and grapevine ( Table 1, Key Table) [ [29][30][31][32][33][34][35][36][37]. Not surprisingly, they have also been examined in domesticated animal species, such as silkworm, sheep, goat, pig, chicken, cow, horse, and dog (Table 1) [22,[38][39][40][41][42][43].…”
Section: Cnvs Are Widespread In Domesticated Speciesmentioning
confidence: 99%
“…Copy number variations related to disease resistance have also been identified in several plant species (Table 2), where disease resistance genes represent a significant fraction of genes in CNV regions and were significantly enriched for resistance gene models (Xu et al 2012;Lu et al 2012). For instance, Boocock et al (2015) have identified 876 CNV regions, which spanned 3.5% of the apple genome and were enriched for genes involved in disease resistance against apple scab. Bertioli et al (2003) showed that in peanut and legumes R-genes have undergone extensive copy number variation.…”
Section: Cnvs and Disease Resistance In Plantsmentioning
confidence: 99%
“…Data so far have focused mostly on domesticated crops of agricultural importance and suggest that although present over thousands of sites, naturally occurring CNV occurs more frequently in gene-poor regions (12) and usually only encompasses a small proportion of the genome. For instance, in apple, maize, and barley, natural CNV has been detected only in 3.5, 10, and 14.9% of the genome, respectively (6,13,14), and therefore does not provide the power to systematically survey the effect of gene dosage variation on plant function.…”
mentioning
confidence: 99%